Mass spectrometry fingerprints for identification of lansium domesticum corr. ethanolic leaf extracts harvested from two different locations / Salfarina Ramli ... [et al.] - Ramli, Salfarina; Saari, Noor Fahimah; Rofiee, Mohd Salleh; Halim, Hasseri; Kek, Teh Lay; Salleh, Mohd Zaki; James, Richard Johari (UiTM Press, 2022)
Lancium domesticum Corr. is a woody tree species from the Meliaceae family and is mainly cultivated for its fruits in Southeast Asia. Parts of the plant have been used in traditional medicine to treat inflammation, gastrointestinal problems, fever, and intestinal worm infection in children. However, phytochemicals in a plant may vary from one location to another due to environmental conditions and soil properties. This study aimed to identify the composition of the L. domesticum ethanolic extracts collected from different locations. L. domesticum leaf ethanolic extracts were prepared from leaves collected from two different locations in Malaysia, namely Perlis and Selangor. Next, the chromatographic pattern and identification of the component from both extracts were carried out by LC/MS-QTOF analysis and accurate mass database screening. The results tentatively identified six compounds, including flavonoid glycosides, phenolics, and terpenes. Interestingly, α, γ- onoceradienedione and lansic acid, onoceranoid triterpenes known to present in the fruit peel of L. domesticum were detected in both leaf extracts. The ion intensity of both compounds was different in both leaf extracts, thus enabling the discrimination of the geographic locations where the L.domesticum leaves were collected. From the results, L. domesticum leaves from Perlis contains more lansic acid and are recommended to be collected for future biological activity studies.